Prevalence of Seismic Rate Anomalies Preceding Volcanic Eruptions in Alaska - Pesicek, Jeremy D.; Wellik, John J.; Prejean, Stephanie G.; Ogburn, Sarah E. (Frontiers in Earth Science, 2018)
Seismic rate increases often precede eruptions at volcanoes worldwide. However, many eruptions occur without such precursors, limiting their usefulness for forecasting in some cases. Additionally, identifying seismic rate increases near volcanoes with high levels of background seismicity is non-trivial and many periods of elevated seismicity occur without ensuing eruptions. Although these issues are commonly known, efforts to quantify them are limited. In this study, we consistently apply a common statistical tool, the -statistic, to seismically monitored eruptions in Alaska of various styles to determine the overall prevalence of seismic rate anomalies immediately preceding eruptions. We find that 6 out of 14 (43%) Volcanic Explosivity Index (VEI) ≥2 eruptions have statistically significant precursory seismic rate increases. Of these 6 eruptions, 4 of them occur at volcanoes with relatively felsic compositions, repose periods greater than 10 years, and VEI ≥ 3. Overall, our results confirm that seismic rate increases are common prior to larger eruptions at long dormant, ‘closed-system’ volcanoes, but uncommon preceding smaller eruptions at more frequently active, ‘open-system’ volcanoes with more mafic magmas. We also explore the rate of other anomalies not precursory to eruptions and investigate their origins. Some of these non-eruptive anomalies can be explained by aftershocks of regional seismic events, magmatic activity that did not lead to eruption, or unrest at other nearby volcanoes within our search radius. Some open-system volcanoes have high non-eruptive anomaly rates and low pre-eruptive anomaly rates and are thus not amenable to forecasting with this method. In this study, we find that 26% of anomalies lead to eruption, while 74% do not. With continued calibration at more volcanoes, the statistical tool that we apply may be used more broadly to analyze future periods of seismic unrest at other volcanoes, properly placing such episodes into the context of the long-term background rate. These results and this tool may be useful for informing future eruption forecasts around the world.